Differentiate the following function
$\displaystyle \frac{5x^2+7x+6}{\sqrt{x}}$
= $\displaystyle \frac{10x+7+0}{x^\frac{1}{2}} $
= $\displaystyle (x^\frac{-1}{2})(10x+7)$
= $\displaystyle 10x^\frac{1}{2}+7x^\frac{-1}{2}$
where am i going wrong?
Differentiate the following function
$\displaystyle \frac{5x^2+7x+6}{\sqrt{x}}$
= $\displaystyle \frac{10x+7+0}{x^\frac{1}{2}} $
= $\displaystyle (x^\frac{-1}{2})(10x+7)$
= $\displaystyle 10x^\frac{1}{2}+7x^\frac{-1}{2}$
where am i going wrong?
$\displaystyle \frac{5x^2 + 7x + 6}{x^{1/2}} = 5x^{3/2} + 7x^{1/2} + 6x^{-1/2}$
Now take the derivative.
You cannot just take the derivative of numerator and leave the denominator. And you cannot just take the derivative of numerator and denominator at the same time. You need to use the quotient rule, if you learned that. But the best is that do what I did.
This is Mine 17th Post!!!